Real-world pharmacovigilance analysis unveils the toxicity profile of amivantamab targeting EGFR exon 20 insertion mutations in non-small cell lung cancer - Jing Zhang; Wenjie Li (BMC Pulmonary Medicine)
Abstract Background While clinical trials have demonstrated enduring responses to amivantamab among advanced non-small cell lung cancer (NSCLC) patients bearing EGFR exon 20 insertion mutations, the associated toxicity profile in real-world scenarios remains elusive. Methods This pharmacovigilance study analyzed data from the FDA Adverse Event Reporting System (FAERS) to investigate adverse events associated with amivantamab over the period from September 2021 to December 2023. A comprehensive disproportionality analysis was performed, employing the reporting odds ratio (ROR), proportional reporting ratio (PRR), Empirical Bayes Geometric Mean (EBGM), and the Bayesian confidence propagation neural network to calculate information components (ICs), to identify statistically significant adverse events. Results A significant proportion of adverse events (AEs) was attributable to injury, poisoning, and procedural complications, cutaneous disorders, respiratory ailments, infections, as well as vascular and lymphatic system disturbances. There were noteworthy incidences of AEs including infusion-related reactions, rash, dyspnea, pneumonitis, paronychia, pulmonary embolism, thrombocytopenia, nausea, acneiform dermatitis, deep vein thrombosis, febrile neutropenia, peripheral edema, hypokalemia, and neutropenia. Furthermore, the majority of AEs occurred within the first month following the initiation of amivantamab treatment, accounting for 51.74% of cases. Conclusion The reversibility of amivantamab-related toxicities suggests its promising utility in patients with EGFR exon 20 insertion mutations NSCLC.